Fluorimetric method for simultaneous estimation of cortisol, corticosterone, and testosterone in plasma. Issue 6 (June 1989) - Mattingly, D; Martin, H; Tyler, C
Abstract : The simultaneous estimation of steroids in plasma was carried out by the assay of cortisol, corticosterone, and testosterone. The method entails separation by means of thin layer chromatography, followed by conversion to a fluorophore and fluorimetric measurement. Its major advantages are its high specificity, its ability to detect unknown substances, and the ease with which it can be performed. The method has acceptable levels of accuracy and precision and the normal values obtained by it compare well with those given by methods in general use.